Long-chain ω-3 fatty acid intake and endometrial cancer risk in the Women's Health Initiative. Issue 4 (4th March 2015) - Brasky, Theodore M; Rodabough, Rebecca J; Liu, Jingmin; Kurta, Michelle L; Wise, Lauren A; Orchard, Tonya S; Cohn, David E; Belury, Martha A; White, Emily; Manson, JoAnn E; Neuhouser, Marian L
ABSTRACT: Background: Inflammation may be important in endometrial cancer development. Long-chain ω-3 (n–3) polyunsaturated fatty acids (LCω-3PUFAs) may reduce inflammation and, therefore, reduce cancer risk. Because body mass is associated with both inflammation and endometrial cancer risk, it may modify the association of fat intake on risk. Objective: We examined whether intakes of LCω-3PUFAs were associated with endometrial cancer risk overall and stratified by body size and histologic subtype. Design: Women were n = 87, 360 participants of the Women's Health Initiative Observational Study and Clinical Trials who were aged 50–79 y, had an intact uterus, and completed a baseline food-frequency questionnaire. After 13 y of follow-up, n = 1253 incident invasive endometrial cancers were identified. Cox regression models were used to estimate HRs and 95% CIs for the association of intakes of individual ω-3 fatty acids and fish with endometrial cancer risk. Results: Intakes of individual LCω-3PUFAs were associated with 15–23% linear reductions in endometrial cancer risk. In women with body mass index (BMI; in kg/m 2 ) <25, those in the upper compared with lowest quintiles of total LCω-3PUFA intake (sum of eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids) had significantly reduced endometrial cancer risk (HR: 0.59; 95% CI: 0.40, 0.82; P -trend = 0.001), whereas there was little evidence of an association in overweight or obese women. The reduction in risk observed in normal-weight women was further specific to type I cancers. Conclusions: Long-chain ω-3 intake was associated with reduced endometrial cancer risk only in normal-weight women. Additional studies that use biomarkers of ω-3 intake are needed to more accurately estimate their effects on endometrial cancer risk. This trial was registered at clinicaltrials.gov as NCT00000611.